Struktur Komunitas Padang Lamun Di Perairan Desa Sadai Kabupaten Bangka Selatan - Fatria Sando; Supratman Okto; Sudirman Adibrata; Okto Supratman (Universitas Bangka Belitung, 2022)
This study aims to determine the conditions of the seagrass beds ecosystem, the physical and chemical conditions, that can be database in the waters of Sadai Village, South Bangka Regency. This research was conducted in July 2019. The data analyzed included: Seagrass cover, seagrass density, seagrass frequency, and Importance Value Index (IVI). The value of seagrass stands in Sadai Village waters is relatively rare. Based on the results obtained, Enhalus acoroides is a type of seagrass that has the ability to adapt well to various water conditions so that it is fairly evenly distributed in the five observation stations. The total percentage of total cover in Sadai Village waters ranges from 5.66% -27.37%. It is known that the highest INP value was also found in the Halodule uninervis seagrass species. Thus, it means that the Halodule uninervis seagrass in Sadai waters has an important meaning as a key species related to the condition of the seagrass community in Sadai Village waters. The seagrass ecosystem in Sadai Village waters is used by local residents as a place to find fish, snails and shellfish. Excessive human activity on the land above can increase the sediment load on water bodies which will result in high turbidity which has the potential to reduce light penetration. This can cause disruption to the primary productivity of the seagrass ecosystem because seagrass requires high light intensity for photosynthesis.